Estimation of effective and organ dose from chest CT. (March 2023) - Almaasfeh, Sultan; Salahudeen, Abdulrahman; Salih, Mohammed; Abukonna, Ahmed
Abstract: The aim of this study was to estimate radiation doses from high resolution chest computed tomography and pulmonary angiography examinations. This retrospective study was conducted between March 2021 and May 2022 for adult patients underwent CT examination in Royal Care Hospital - Sudan. A total of 180 patients were examined with 64-slice CT system (Aquilion 64, Toshiba Medical System Corporation). Data was collected using a validated survey, including scanner information, patient demographic data, scan protocol, and dose indices (CT dose index volume (CTDIvol ) and dose length product (DLP)). Effective and organ doses were calculated by VirtualDose software based on ICRP 103. The result of the study revealed that CTDIvol for high resolution chest computed tomography and pulmonary angiography were 15.41 mGy and 14.61 mGy respectively. DLP were 476.5 mGy/cm and 520 mGy/cm, respectively. The calculated effective doses (ED) were 8.95 mSv and 8.57 mSv, respectively. The highest organ dose was recorded in the heart (20.09 mGy) and the lowest at the thyroid (3.41 mGy). The reported measurements provide a variety of data that CT departments can use for efforts aimed at quality improvement. Dose calculation software facilitates efficient documentation and comparison of local radiation dose data with national DRLs and helps to implement optimization if DRLs are exceeded the limits. Highlights: Radiation effective dose for patients undergoing HRCT chest and CT Pulmonary Angiography. Organ Dose for heart, lung, breast and Thyroid. Dose delivered to patients found to be within the range reported in literature. Variation in doses due to protocol settings.